(untitled) (Revista de Estudos da Linguagem, 2024)
In the light of materialist Discourse Analysis, in its relationship with the History of Linguistic Ideas, we will reflect on the functioning of the sayings broadcasted on 11/9/2018 by the newly elected presidential candidate’s Youtube channel about what he named “gender ideology” when commenting an Enem question. Our objective is to relate some regularities observed in these sayings with what we are trying to formulate as a Bolsonarist discourse. Therefore, we have established three starting questions: 1) how are the speaker, interlocutor and object of these sayings signified in the speech of the elected candidate?; 2) what are the policies announced for Enem and how do they articulate with this imaginary?; and, 3) how does the 2018 commentary relate to the one on the 2021 edition carried out in the third year of his term? The analysis pointed out elements that strengthen our hypothesis of a “bolsonarist discourse”, such as: the projection of two others – an interlocutor and an object, signified as an enemy to be fought –; and the articulation of positions affiliated to different discourses (conservative, (neo)liberal, nationalist, religious) from which a new way of enunciating and, therefore, of becoming a subject is established.